KAJIAN DISTRIBUSI MAKROFAUNA BERDASARKAN KEKAYAAN, KEANEKARAGAMAN, DAN KEMERATAAN JENIS DI KAWASAN TAMAN KUPU-KUPU GITA PERSADA, TELUK BETUNG UTARA, BANDAR LAMPUNG - Azizah, Finda Hasna; Melani, Tira; Azzahra, Kanaya Syaftia; Handayani, Liska; Fadillah, Rismatul; Putri, Dwi Kartika; Ayu, Niluh Putu Sekar; Joda, Nur Fadilla; Priyambodo, Panggih; Priadi, Median Agus (Universitas Jambi, 2026)
Habitats with good ecological conditions are closely associated with the distribution of macrofauna, which play an important role in maintaining ecosystem stability. This study aims to investigate the distribution of macrofauna based on species richness, diversity, and evenness in Gita Persada Butterfly Park, Teluk Betung Utara, Bandar Lampung. The line transect method combined with sweep net and pitfall trap techniques was applied in this study. The results showed differences across sampling points. At nectar points using the sweep net technique, a high category was obtained for the richness index (7.847), diversity index (3.176), and evenness index (0.908). Furthermore, the evenness index at edge points also obtained the highest category (0.964). The richness index at nectar points using the pitfall trap technique obtained a low category (3.284), whereas at vegetation stands, the highest values were obtained for the diversity index (1.864) and evenness index (0.809). These findings indicate that the distribution of macrofauna can reflect environmental conditions and habitat quality.